2003
DOI: 10.1007/s00125-003-1062-3
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of conditional insulinoma cell lines in NOD mice: A role for autoimmunity

Abstract: Aims/Hypothesis. βTC-tet (H2 k ) is a conditional insulinoma cell line derived from transgenic mice expressing a tetracycline-regulated oncogene. Transgenic expression of several proteins implicated in the apoptotic pathways increase the resistance of βTC-tet cells in vitro. We tested in vivo the sensitivity of the cells to rejection and the protective effect of genetic alterations in NOD mice. Methods. βTC-tet cells and genetically engineered lines expressing Bcl-2 (CDM3D), a dominant negative mutant of MyD88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Furthermore, we found that a similar degree of hypocellularity (thymus and spleen) can be generated by causing diabetes via removal of the islet transplant. In terms of immune function, our data showed that the previously described reduced ability of STZ‐treated mice to reject allogeneic β TC‐tet tumour cells [2, 3] or in some cases whole islet transplants, can be reversed by curing diabetes with syngeneic islet transplants.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, we found that a similar degree of hypocellularity (thymus and spleen) can be generated by causing diabetes via removal of the islet transplant. In terms of immune function, our data showed that the previously described reduced ability of STZ‐treated mice to reject allogeneic β TC‐tet tumour cells [2, 3] or in some cases whole islet transplants, can be reversed by curing diabetes with syngeneic islet transplants.…”
Section: Discussionmentioning
confidence: 66%
“…Lentiviral-mediated cFLIP overexpression in another murine ␤-cell line (NIT-1) has also been shown to prevent cytokine-mediated ␤-cell death in vitro (40). However, the in vitro benefit of cFLIP overexpression in islet ␤-cells has not been observed in vivo (41). This disappointing observation can most likely be attributed to the recent finding that cFLIP has a dual functionality that depends on expression levels and can, under some circumstances, actually promote apoptosis.…”
Section: Genetic Manipulations To Prevent 〉-Cell Apoptosismentioning
confidence: 99%
“…However, these promising results have been met with mixed outcomes in animal models of transplantation. Adenovirally mediated BCL-2 overexpression in macaque islets reduced the number of islets necessary to reverse diabetes in chemically diabetic nude mice, while ␤TC-Tet cells stably transfected with BCL-2 exhibited no survival advantage in vivo, despite enhanced proliferative capacity (41,48,51). Another antiapoptotic BCL-2 family member, BCL-XL, has proven to be effective in preventing apoptosis triggered by IL-1␤, staurosporine, and serum withdrawal in vitro (52).…”
Section: Genetic Manipulations To Prevent 〉-Cell Apoptosismentioning
confidence: 99%
“…The impact of anti‐apoptotic genes in the acute post‐transplant period remains unknown. The mitochondrial apoptotic pathway inhibitors Bcl‐2 and Bcl‐XL have been shown to prevent β‐cell death from hypoxia and/or proinflammatory cytokines in vitro , but have failed to prevent allograft rejection in vivo (11–13). A20, which inhibits NF‐κB activation, has been shown to protect β‐cells from cytokine‐ and Fas‐mediated killing in vitro , and to reduce the β‐cell mass required for syngeneic islet transplantation (14,15).…”
Section: Introductionmentioning
confidence: 99%